2022
DOI: 10.1155/2022/9000608
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Anti-SAE1 Dermatomyositis

Abstract: Introduction. Anti-SAE1 antibodies have a low prevalence in dermatomyositis patients. Case Description. A 61-year-old woman presented with progressive shortness of breath, arthralgia, heliotrope rash, Gottron’s papules, and erythematous rash. She had an interstitial lung disease (ILD) with a significant decrease in lung function. There was no muscle involvement. Immunological laboratory test results showed strongly positive anti-SAE1 antibodies. Glucocorticoid treatment resulted in remission of dermatomyositis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Pulmonary involvement is variable in DM according to different MSA and is mainly associated with the anti-MDA5 subset, where it often presents as nonspecific interstitial pneumonia and car-ries a high risk of developing into rapidly progressive ILD (21). It is important to emphasise that the primary type of ILD reported in anti-SAE DM is organising pneumonia (22), typically characterised by a chronic course and a favourable prognosis (23,24). However, we observed a case of rapidly progressive ILD that led to death.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary involvement is variable in DM according to different MSA and is mainly associated with the anti-MDA5 subset, where it often presents as nonspecific interstitial pneumonia and car-ries a high risk of developing into rapidly progressive ILD (21). It is important to emphasise that the primary type of ILD reported in anti-SAE DM is organising pneumonia (22), typically characterised by a chronic course and a favourable prognosis (23,24). However, we observed a case of rapidly progressive ILD that led to death.…”
Section: Discussionmentioning
confidence: 99%
“…
The frequency of anti-SAE1 (small ubiquitin-like modifier activating enzyme) in dermatomyositis (DM) patients is very low, ranging from 1.5% to 8.0%. 1 The typical phenotype is usually that of widespread skin involvement with amyopathic or mild muscle involvement. The association with interstitial lung disease (ILD), dysphagia, other extramuscular involvement, and cancer varies per cohort.
…”
mentioning
confidence: 99%
“…5 ILD associated with anti-SAE antibodies is characterized by an insidious clinical course with few respiratory complaints, a preserved pulmonary function, and a limited extent of pulmonary lesions with subpleural peripheral-dominant small ground glass opacities/consolidations on chest CT. 6 Most studies on anti-SAE1 antibodies and cancer show a positive association. A study by De Vries et al 1 indicated that most patients suffered from adenocarcinoma of cervical, ovarian, pulmonary, esophageal, or rectal origin. Therefore, all patients diagnosed with anti-SAE DM should undergo an age and sex-appropriate malignancy workup.…”
mentioning
confidence: 99%